Two species of the conifera-subgroup of Triconia (Copepoda, Oncaeidae) from the northeastern equatorial Pacific, with a description of the unknown male of T. hirsuta - Cho, Kyuhee; Böttger-Schnack, Ruth; Kim, Woong-Seo; Lee, Wonchoel (Zootaxa, 2017)
We describe two species from the genus Triconia Böttger-Schnack, 1999 in the family Oncaeidae from the northeastern equatorial Pacific, both belonging to the conifera-subgroup. Both sexes of T. derivata (Heron & Bradford-Grieve, 1995) are redescribed, including morphological features not noted in earlier descriptions, such as the posterior face of the labrum. Specimens of T. derivata from the northeastern equatorial Pacific differ slightly from the original descriptions in some morphometric characters, and their differentiation from T. furcula (Farran, 1936), which is closely related, is summarized. The male of T. hirsuta Wi, Böttger-Schnack & Soh, 2010 is described for the first time and the morphology of the female is redescribed. The female holotype of T. hirsuta from Korean waters is reexamined and discrepancies between text and figures in the original description regarding the endopodal spine lengths on swimming leg 2 are clarified. A revised version of the respective part of the original figure is included in the present paper. An indication of the variation in endopodal spine lengths on swimming legs 2 to 4 is provided for both sexes of the two species. It is pointed out that morphometric characters required for unequivocal identification of species of the conifera-subgroup are still not sufficiently well defined. The records of T. derivata and T. hirsuta to date are summarized and indicate a wide zoogeographical distribution of the former species.